In vitro and in situ activation of the complement system by the fungus Lacazia loboi - Vilani-Moreno, Fátima Regina; Mozer, Érika; Sene, Ana Márcia Guedes de; Ferasçoli, Margarete de Oliveira; Pereira, Tânia Cristina; Miras, Márcia Garcia; Souza, Gláucia Heloísa de Paula; Belone, Andréa de Faria Fernandes (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
Since there are no studies evaluating the participation of the complement system (CS) in Jorge Lobo's disease and its activity on the fungus Lacazia loboi, we carried out the present investigation. Fungal cells with a viability index of 48% were obtained from the footpads of BALB/c mice and incubated with a pool of inactivated serum from patients with the mycosis or with sterile saline for 30 min at 37 ºC. Next, the tubes were incubated for 2 h with a pool of noninactivated AB+ serum, inactivated serum, serum diluted in EGTA-MgCl2, and serum diluted in EDTA. The viability of L. loboi was evaluated and the fungal suspension was cytocentrifuged. The slides were submitted to immunofluorescence staining using human anti-C3 antibody. The results revealed that 98% of the fungi activated the CS by the alternative pathway and no significant difference in L. loboi viability was observed after CS activation. In parallel, frozen histological sections from 11 patients were analyzed regarding the presence of C3 and IgG by immunofluorescence staining. C3 and IgG deposits were observed in the fungal wall of 100% and 91% of the lesions evaluated, respectively. The results suggest that the CS and immunoglobulins may contribute to the defense mechanisms of the host against L. loboi.